PilY1 Promotes Legionella pneumophila Infection of Human Lung Tissue Explants and Contributes to Bacterial Adhesion, Host Cell Invasion, and Twitching Motility - Hoppe, Julia; Ünal, Can M.; Thiem, Stefanie; Grimpe, Louisa; Goldmann, Torsten; Gaßler, Nikolaus; Richter, Matthias; Shevchuk, Olga; Steinert, Michael (Frontiers in Cellular and Infection Microbiology, 2017)
Legionnaires´ disease is an acute fibrinopurulent pneumonia. During infection L. pneumophila adheres to the alveolar lining and replicates intracellularly within recruited macrophages. Here we provide a sequence and domain composition analysis of the L. pneumophila PilY1 protein, which has a high homology to PilY1 of Pseudomonas aeruginosa. PilY1 proteins of both pathogens contain a von Willebrand factor A (vWFa) and a C-terminal PilY domain. Using cellular fractionation, we assigned the L. pneumophila PilY1 as an outer membrane protein that is only expressed during the transmissive stationary growth phase. PilY1 contributes to infection of human lung tissue explants (HLTEs). A detailed analysis using THP-1 macrophages and A549 lung epithelial cells revealed that this contribution is due to multiple effects depending on host cell type. Deletion of PilY1 resulted in a lower replication rate in THP-1 macrophages but not in A549 cells. Further on, adhesion to THP-1 macrophages and A549 epithelial cells was decreased. Additionally, the invasion into non-phagocytic A549 epithelial cells was drastically reduced when PilY1 was absent. Complementation variants of a PilY1-negative mutant revealed that the C-terminal PilY domain is essential for restoring the wild type phenotype in adhesion, while the putatively mechanosensitive vWFa domain facilitates invasion into non-phagocytic cells. Since PilY1 also promotes twitching motility of L. pneumophila, we discuss the putative contribution of this newly described virulence factor for bacterial dissemination within infected lung tissue.